Casper - Silberling, Brad.; Universal Pictures ([s.l.] Universal Pictures, 1995)
Casper is a friendly but lonely young ghost who can't seem to help scaring people. Then, one day, two new visitors show up on the doorstep of his fantastically hunted house, Whipstaff Manor, Kat Harvey and her eccentric dad, Dr. Harvey, a self-styled ghost therapist. Whipstaff's scheming owner, Carrigan Crittenden, has hired Harvey to exorcise the house's spectral inhabitants so that she can get hands on the manor's fabled treasure. Unfortunately Dr. Harvey, the ghostly trio--Fatso, Stinkie, and Stretch have their own methods of getting rid of unwanted visitors and a certifiably twisted sense of humor.
VCD
Screenplay by Sherri Stoner, Deanna Oliver ; producer, Colin Wilson ; directed by Brad Silberling
Christina Ricci, Bill Pullman, Cathy Moriarty, Eric Idle
Keywords: Feature films; Fantasy comedies